Analisis Pemanfaatan Media Digital Terhadap Pemahaman Literasi Baca Tulis Calon Guru - Fasya Amalia Pitaloka; Intan Dwiyanti; Linda Supriatin; Andina Aisyah Eka Jati; Weby Khamelia; Sofyan Iskandar; Neneng Sri Wulan; Nuur Wachid Abdul Majid (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
According to UNESCO data, it is explained that Indonesia ranks second from the bottom, because literacy is very low, namely only 0.001%. Indonesia has a very low percentage in literacy. This study uses qualitative research, with a descriptive method. Data collection was carried out by distributing questionnaires to student teacher candidates. Based on the diagram, it shows that 90 respondents (100%) stated that digital media had an effect on understanding of literacy. The demands of technological developments make students study digital media for classroom learning. the use of digital media is important to use as a provision to face the times. As a prospective teacher, you should know more about digital media in the surrounding environment to make it easier when making teaching materials and developing learning